Mengurai Polemik Abadi Absolutisme dan Relativisme Etika - Fahmi Farid Purnama (Living Islam: Journal of Islamic Discourses, 2018)
Arthur Schopenhauer described teaching morality is not as difficult as giving bases its foundations. As the hope of humanity, the base of ethics is something that always aspired to every thinker. But the base of universal ethics and without contradiction is impossible to achieve. In the development of the ethics in such a complicated, especially related to the complexity of ethical relativism and absolutism among ethical—in fact—become an endless polemic among philosophers. By basing on the differences of culture, proponents of relativism presup- poses a moral basis ' without basis ' (groundless ethic). While the absolutist trying to affirm a moral basis which is released from the actual situation as well as the limits of his humanity.